First Aid Education Guidelines for the General Approach: Integrating Physical and Mental Care in Approaching any First Aid Situation (International Journal of First Aid Education)
The International First Aid, Resuscitation and Education Guidelines 2020 (IFRC, 2020) brought together not only the relevant evidence base for a particular clinical intervention, but also the evidence that underpins first aid education approaches. This synthesis ensures accessibility of learning and the ability for learners to apply it to their own unique contexts and an acknowledgement that if we are to achieve resilient communities where individuals feel able to intervene in a crisis, we must ensure a parity between clinical familiarity and enabling confidence in learners via relevant and adaptive first aid education. The IFRC Guidelines (2020) embed the “General Approach” as a foundation for providing care to all involved in a first aid situation. Through the general approach, the first aider assesses the scene and the person, making critical and dynamic decisions to keep themselves and others safe. The inclusion of psychological first aid in this recognizes that all first aid interventions have the potential to be emotionally challenging, and outlines strategies for promoting self-care and mental wellness when responding to a crisis. In this paper, the Chain of Survival Behaviors and core educational principles of link to learners, variety, simplicity & clarity, discovery, and outcome driven, are used to explore the context of the general approach and psychological first aid. Challenges and barriers, such as stigma and facilitator confidence are then discussed, along with and navigating the ‘grey space’ in order to achieve true inclusive, effective and equitable first aid education practice.